2022
DOI: 10.3389/fmars.2022.862379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Curcumin on Growth and Digestive Physiology of Seriola dumerili

Abstract: In order to understand the effects of dietary curcumin on the growth and digestive performance of Seriola dumerili, this study was conducted under laboratory conditions. The control group was added with 0% curcumin, and two treatment groups were added with 0.01% and 0.02% curcumin, respectively. Fish were fed with experimental diet for 8 weeks. The growth data, growth genes, intestinal digestive enzymes, tissue parameters, and blood lipid-related indicators were measured, and the correlation between digestive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…This suggests that curcumin enhances the absorption of nutrients by improving intestinal integrity. This is also consistent with the results of our other experiment in which dietary supplementation with curcumin significantly improved intestinal digestive enzymes activity (lipase and trypsin) [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that curcumin enhances the absorption of nutrients by improving intestinal integrity. This is also consistent with the results of our other experiment in which dietary supplementation with curcumin significantly improved intestinal digestive enzymes activity (lipase and trypsin) [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Speci cally, our study found that glucose, triglyceride, and total cholesterol levels have notably decreased in Nile tilapia upon feeding with various doses of Cu-NPs-supplemented diets (Abdel-Tawwab et al 2022). Curcumin and Spirulina platensis have both been found to reduce triglyceride and total cholesterol in sh species such as tilapia, grass carp, and amberjack Seriola dumerili (Yang et al 2022). Also, we found that curcumin has a bene cial regulatory impact on lipid metabolism, decreasing the production of cholesterol and triglycerides in the liver and plasma (Shin et Many diseases and inescapable environmental pollutants endanger the well-being of sh (Taghreed 2019).…”
Section: Discussionmentioning
confidence: 78%
“…The ND 5000 spectrophotometer (BioTeke Corporation, China) and 1% agarose gel electrophoresis were used to evaluate the quantity and integrity of isolated RNA, respectively. Finally, the reverse transcription and relative gene expression were determined according to the method of Yang, et al 67 .…”
Section: Methodsmentioning
confidence: 99%